Robust Backstepping Control of Robot Manipulator in Task Space with Uncertainties in Kinematics and Dynamics - Soltanpour, M. R.; Shafiei, S. E. (Elektronika ir Elektrotechnika, 2009)
This paper introduces a novel robust control approach for trajectory tracking of robot manipulator in task space. A new task space control scheme is proposed to overcome the uncertainties in robot dynamics and kinematics. A robust controller is designed based on Lyapunov method, using backstepping method. It is then proven that the closed loop system has global uniform ultimate boundedness stability. Modifications are given to derive a control law which is free of position and velocity of end-effector. The control approach is applied on a two-links elbow robot manipulator. The performance of proposed control laws are confirmed by simulations. Ill. 8, bibl. 13, tabl. 1 (in English; abstracts in English, Russian and Lithuanian).